2017
DOI: 10.1111/bju.14044
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of open radical cystectomy versus robot‐assisted radical cystectomy

Abstract: High ongoing equipment costs remain a large barrier to the cost of RARC falling. However, minimal improvements in patient quality of life would be required to offset this difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
(50 reference statements)
0
27
0
Order By: Relevance
“…The perceived additional cost associated with robotic surgery is a common argument against adopting the technology. Although the robot itself, the consumables and maintenance are a considerable financial investment, there are numerous examples, where robotic surgery has proven to be cost effective in high volume centres [58, 59] or even cost saving [60, 61], be it within certain, realistic, anticipated complication levels. Although the financial comparison between LAG and OG has not been formally assessed (although expected as part of the LOGICA trial), the cost of RAG was compared to LAG in a multicentre prospective match cohort study and found to be around $5000 higher ($13432 vs $8090) [17].…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…The perceived additional cost associated with robotic surgery is a common argument against adopting the technology. Although the robot itself, the consumables and maintenance are a considerable financial investment, there are numerous examples, where robotic surgery has proven to be cost effective in high volume centres [58, 59] or even cost saving [60, 61], be it within certain, realistic, anticipated complication levels. Although the financial comparison between LAG and OG has not been formally assessed (although expected as part of the LOGICA trial), the cost of RAG was compared to LAG in a multicentre prospective match cohort study and found to be around $5000 higher ($13432 vs $8090) [17].…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…With many units now routinely performing intracorporeal urinary diversion (ICUD), further benefits can be derived by a reduction in incision size, postoperative pain, and bowel-related complications [10] . A recent study demonstrated that introduction of RARC and ICUD represented the principal factor leading to the benefits of a RC enhanced-recovery programme [11] , and furthermore cost-efficiency analyses have shown promising results even when factoring in purchase, consumable and maintenance expenses [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…We initially identified 315 studies from PubMed, Web of Science, and Cochrane Library databases. Of the 315 studies, 11 were included in this study [11, 13, 1927]. The characteristics of the included studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies compared ORC to LRC [19, 20], and nine compared ORC to RARC [11, 13, 2127]. Of the studies that compared ORC to RARC, four were single-institutional retrospective studies [11, 13, 21, 22], one was a single-institutional RCT [23], and the remaining four were administrative large database studies [2427]. The QOL was measured in one study [23] and no significant difference in QOL scores between ORC and RARC was found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation